A high voltage window linear coaxial structure supercapacitor and preparation method thereof

The problem of electrode separation and low voltage windows is solved by using activated carbon-coated carbon fiber wire and nickel foil in linear supercapacitors, which is suitable for wearables by combining ionic liquid gel electrolytes. equipment.

CN114300278BActive Publication Date: 2025-01-03JIANGSU MENGZHENG MEDICAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111655744.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-30
Publication Date
2025-01-03
Estimated Expiration
2041-12-30

AI Technical Summary

Technical Problem

The electrodes of existing linear supercapacitors are easily separated during bending, have high contact impedance, and have low working voltage, which limits their energy density and electrochemical stability, and cannot meet the practical application needs.

Method used

Use activated carbon-coated carbon fiber wire and nickel foil as internal and external electrodes, and combined with ionic liquid gel as solid electrolytes, a linear coaxial structure supercapacitor with high voltage window was prepared, and a stable electrode structure was formed by uniform coating and vacuum drying.

Benefits of technology

It realizes high voltage window, excellent flexibility and electrochemical stability, improves energy density and mechanical properties, and ensures stable electrochemical performance under different bending conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114300278B_ABST
    Figure CN114300278B_ABST
Patent Text Reader

Abstract

The present invention discloses a high voltage window linear coaxial structure supercapacitor and a preparation method thereof, wherein the supercapacitor comprises a carbon fiber wire located at the center and a nickel foil wrapped around the outer surface of the carbon fiber wire, and an ionic liquid gel is filled between the carbon fiber wire and the nickel foil, wherein the carbon fiber wire serves as an inner electrode, the nickel foil serves as an outer electrode, and the ionic liquid gel serves as a solid electrolyte. The preparation method adopts a coating method to effectively assemble the supercapacitor, and after the assembly is completed, a linear supercapacitor with a coaxial structure is prepared. The linear supercapacitor prepared by the present invention can be widely used in the field of energy storage with flexibility, foldability, easy wearability and portability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a high voltage window linear coaxial structure super capacitor and a preparation method thereof Background Art

[0002] With the development of smart wearables, flexible energy storage devices have become one of the research hotspots in the field of new energy. Among flexible energy storage devices, linear supercapacitors have attracted the attention of researchers with their excellent performance.

[0003] Linear supercapacitors have the advantages of small size, light weight, high flexibility, and easy wearability. In addition, linear supercapacitors have fast charging and discharging capabilities and ultra-long service life comparable to traditional supercapacitors.

[0004] Therefore, the research and development of linear supercapacitors is of great significance for the application of wearable electronic devices.

[0005] Current research work is to coat or grow electroactive materials on two linear substrates to obtain linear electrodes, and then wrap them together to prepare linear supercapacitors. However, the two wrapped linear electrodes are easy to separate during the bending process, and there is a high contact impedance, which greatly affects the mechanical properties and electrochemical stability of the linear supercapacitor. In addition, the linear supercapacitors currently studied are limited by their low operating voltage, which usually does not exceed 2.5V, which greatly limits their specific energy. The low potential window causes the energy density of linear supercapacitors to be unable to meet the needs of practical applications. Summary of the invention

[0006] The purpose of the present invention is to solve the above deficiencies in the prior art and to provide a high voltage window linear coaxial structure supercapacitor and a preparation method thereof.

[0007] A high voltage window linear coaxial structure supercapacitor, in which activated carbon-coated carbon fiber wire and nickel foil are used as inner and outer electrodes respectively, and ionic liquid gel is used as solid electrolyte. The prepared linear coaxial structure supercapacitor has a high voltage window and high energy density, and exhibits good flexibility and excellent electrochemical stability.

[0008] The method for preparing the supercapacitor comprises the following steps:

[0009] Step 1: Mix the activated carbon and the conductive agent, then add the binder and water and stir to form a slurry;

[0010] Step 2: Take an equal amount of the slurry obtained in step 1 and evenly coat it on the flexible carbon fiber wire and nickel foil respectively, and vacuum dry it for 24 hours to obtain the carbon fiber wire and nickel foil coated with activated carbon;

[0011] Step 3, using N-methoxyethyl-N-methyldiethylammonium tetrafluoroborate to prepare an ionic liquid gel electrolyte;

[0012] Step 4: Use the carbon fiber wire coated with activated carbon obtained in step 2 as the inner electrode, and coat the surface of the carbon fiber wire with a dense solid ionic liquid gel electrolyte;

[0013] Step 5: Use the activated carbon-coated nickel foil obtained in step 2 as the outer electrode, evenly wrap it on the inner electrode covered with the ionic liquid gel obtained in step 3, and vacuum dry it for 6 hours to obtain a linear coaxial structure supercapacitor.

[0014] Furthermore, the mass fractions of activated carbon, acetylene black conductive agent and polyacrylic acid binder in the slurry in step one are 85%, 5% and 10% respectively.

[0015] Furthermore, the mass of the slurry in step 2 is 6 to 30 mg.

[0016] Furthermore, the diameter of the carbon fiber wire in step 2 is 0.2 cm and the length is 3 to 9 cm.

[0017] Furthermore, the nickel foil in step 2 has a width of 1 cm and a length of 3 to 9 cm.

[0018] Furthermore, the drying temperature in step 2 is 80-160°C.

[0019] Furthermore, the drying temperature in step five is 40-60°C.

[0020] Beneficial effects:

[0021] 1. Carbon fiber wire and nickel foil are used as flexible substrates, and a relatively mature and controllable coating method is adopted for production and preparation, so that the prepared electrodes not only have a high loading amount of electroactive materials, but also have controllable volume and size.

[0022] 2. The linear supercapacitor disclosed in the present invention has a coaxial structure, which can ensure that the linear supercapacitor has stable mechanical properties, low contact impedance and good electrochemical stability.

[0023] 3. Compared with other flexible energy storage devices, the linear supercapacitor prepared by this method has a wide voltage window and high energy density, as well as excellent flexibility and electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a schematic diagram of the assembly of the linear coaxial structure supercapacitor prepared in Example 1;

[0025] Figure 2is a cyclic voltammetry curve of the linear coaxial structure supercapacitor prepared in Example 1;

[0026] Figure 3 is a charge and discharge curve diagram of the linear coaxial structure supercapacitor prepared in Example 1 at different current densities;

[0027] Figure 4 is a three-dimensional graph of energy density and power density of the linear coaxial structure supercapacitor prepared in Example 1 at different current densities;

[0028] Figure 5 1 is a cyclic voltammetry curve of the linear coaxial structure supercapacitor prepared in Example 1 under different bending conditions;

[0029] Figure 6 1 is the cycle performance curve of the linear coaxial structure supercapacitor prepared in Example 1;

[0030] 1. Nickel foil 2. Carbon fiber wire 3. Ionic liquid gel. DETAILED DESCRIPTION

[0031] The following will disclose the embodiments of the present invention with drawings. For the purpose of clear description, many practical details will be described together in the following description. However, it should be understood that these practical details should not be used to limit the present invention. That is, in some embodiments of the present invention, these practical details are not necessary. In addition, for the purpose of simplifying the drawings, some conventional structures and components will be depicted in a simple schematic manner in the drawings.

[0032] Embodiment 1:

[0033] Mix the activated carbon and acetylene black conductive agent thoroughly, then add polyacrylic acid binder and water, and stir at room temperature for 24 hours to form a slurry. The mass fractions of activated carbon, conductive agent and binder are ensured to be 85%, 5% and 10% respectively;

[0034] 18 mg of the slurry was evenly coated on a carbon fiber line with a diameter of 0.2 cm and a length of 6 cm. At the same time, an equal amount of the slurry was evenly coated on a nickel foil with a width of 1 cm and a length of 6 cm. The activated carbon-coated carbon fiber line and nickel foil were obtained by vacuum drying at 120° C. for 24 hours.

[0035] 0.52 g of vinylidene fluoride-hexafluoropropylene copolymer and 1.86 g of N-methoxyethyl-N-methyldiethylammonium tetrafluoroborate were dissolved in 5 mL of acetone and stirred at room temperature for 10 hours to obtain a viscous ionic liquid gel electrolyte;

[0036] The carbon fiber wire coated with activated carbon is used as the inner electrode, and a dense layer of ionic liquid gel electrolyte is evenly coated on its surface;

[0037] The nickel foil coated with activated carbon was used as the outer electrode, evenly wrapped on the inner electrode covered with the ionic liquid gel, and vacuum dried at 50°C for 6 hours to obtain a linear coaxial structure supercapacitor.

[0038] like Figure 1 As shown, activated carbon-coated carbon fiber wires and nickel foil serve as the inner and outer electrodes, respectively, and ionic liquid gel serves as the solid electrolyte.

[0039] Figure 2-4 This is a characterization diagram of the electrochemical performance of the linear coaxial structure supercapacitor obtained in Example 1. The results show that this linear coaxial structure supercapacitor has excellent electrochemical performance and a high voltage window (0-4.5V), and its maximum energy density can reach 91.1Wh / kg and its power density is as high as 18.12kW / kg.

[0040] Figure 5 1 is the cyclic voltammetry curve of the linear coaxial structure supercapacitor obtained in Example 1 under different bending conditions.

[0041] It can be seen that the shape of the cyclic voltammetry curve does not change significantly at different bending angles, which indicates that the linear coaxial structure supercapacitor obtained in this embodiment can still maintain stable electrochemical performance when subjected to different bending.

[0042] Figure 6 This is the cycle stability curve of the linear coaxial structure supercapacitor obtained in Example 1.

[0043] After 4000 cycles of charge and discharge, the capacitance retention rate of the linear coaxial structure supercapacitor can still be maintained at about 96% of the initial capacity.

[0044] Example 2

[0045] Mix the activated carbon and acetylene black conductive agent thoroughly, then add polyacrylic acid binder and water, and stir at room temperature for 24 hours to form a slurry. The mass fractions of activated carbon, conductive agent and binder are ensured to be 85%, 5% and 10% respectively;

[0046] 6 mg of the slurry was evenly coated on a carbon fiber line with a diameter of 0.2 cm and a length of 6 cm. At the same time, an equal amount of the slurry was evenly coated on a nickel foil with a width of 1 cm and a length of 6 cm. The activated carbon-coated carbon fiber line and nickel foil were obtained by vacuum drying at 120° C. for 24 hours.

[0047] 0.52 g of vinylidene fluoride-hexafluoropropylene copolymer and 1.86 g of N-methoxyethyl-N-methyldiethylammonium tetrafluoroborate were dissolved in 5 mL of acetone and stirred at room temperature for 10 hours to obtain a viscous ionic liquid gel electrolyte;

[0048] The carbon fiber wire coated with activated carbon is used as the inner electrode, and a dense layer of ionic liquid gel electrolyte is evenly coated on its surface;

[0049] The nickel foil coated with activated carbon was used as the outer electrode, evenly wrapped on the inner electrode covered with the ionic liquid gel, and vacuum dried at 50°C for 6 hours to obtain a linear coaxial structure supercapacitor.

[0050] Example 3

[0051] Mix the activated carbon and acetylene black conductive agent thoroughly, then add polyacrylic acid binder and water, and stir at room temperature for 24 hours to form a slurry. The mass fractions of activated carbon, conductive agent and binder are ensured to be 85%, 5% and 10% respectively;

[0052] 30 mg of the slurry was evenly coated on a carbon fiber line with a diameter of 0.2 cm and a length of 6 cm. At the same time, an equal amount of the slurry was evenly coated on a nickel foil with a width of 1 cm and a length of 6 cm. The activated carbon-coated carbon fiber line and nickel foil were obtained by vacuum drying at 120° C. for 24 hours.

[0053] 0.52 g of vinylidene fluoride-hexafluoropropylene copolymer and 1.86 g of N-methoxyethyl-N-methyldiethylammonium tetrafluoroborate were dissolved in 5 mL of acetone and stirred at room temperature for 10 hours to obtain a viscous ionic liquid gel electrolyte;

[0054] The carbon fiber wire coated with activated carbon is used as the inner electrode, and a dense layer of ionic liquid gel electrolyte is evenly coated on its surface;

[0055] The nickel foil coated with activated carbon was used as the outer electrode, evenly wrapped on the inner electrode covered with the ionic liquid gel, and vacuum dried at 50°C for 6 hours to obtain a linear coaxial structure supercapacitor.

[0056] Example 4

[0057] Mix the activated carbon and acetylene black conductive agent thoroughly, then add polyacrylic acid binder and water, and stir at room temperature for 24 hours to form a slurry. The mass fractions of activated carbon, conductive agent and binder are ensured to be 85%, 5% and 10% respectively;

[0058] 18 mg of the slurry was evenly coated on a carbon fiber line with a diameter of 0.2 cm and a length of 3 cm. At the same time, an equal amount of the slurry was evenly coated on a nickel foil with a width of 1 cm and a length of 3 cm. The activated carbon-coated carbon fiber line and nickel foil were obtained by vacuum drying at 120° C. for 24 hours.

[0059] 0.52 g of vinylidene fluoride-hexafluoropropylene copolymer and 1.86 g of N-methoxyethyl-N-methyldiethylammonium tetrafluoroborate were dissolved in 5 mL of acetone and stirred at room temperature for 10 hours to obtain a viscous ionic liquid gel electrolyte;

[0060] The carbon fiber wire coated with activated carbon is used as the inner electrode, and a dense layer of ionic liquid gel electrolyte is evenly coated on its surface;

[0061] The nickel foil coated with activated carbon was used as the outer electrode, evenly wrapped on the inner electrode covered with the ionic liquid gel, and vacuum dried at 50°C for 6 hours to obtain a linear coaxial structure supercapacitor.

[0062] Example 5

[0063] Mix the activated carbon and acetylene black conductive agent thoroughly, then add polyacrylic acid binder and water, and stir at room temperature for 24 hours to form a slurry. The mass fractions of activated carbon, conductive agent and binder are ensured to be 85%, 5% and 10% respectively;

[0064] 18 mg of the slurry was evenly coated on a carbon fiber line with a diameter of 0.2 cm and a length of 9 cm. At the same time, an equal amount of the slurry was evenly coated on a nickel foil with a width of 1 cm and a length of 9 cm. The activated carbon-coated carbon fiber line and nickel foil were obtained by vacuum drying at 120° C. for 24 hours.

[0065] 0.52 g of vinylidene fluoride-hexafluoropropylene copolymer and 1.86 g of N-methoxyethyl-N-methyldiethylammonium tetrafluoroborate were dissolved in 5 mL of acetone and stirred at room temperature for 10 hours to obtain a viscous ionic liquid gel electrolyte;

[0066] The carbon fiber wire coated with activated carbon is used as the inner electrode, and a dense layer of ionic liquid gel electrolyte is evenly coated on its surface;

[0067] The nickel foil coated with activated carbon was used as the outer electrode, evenly wrapped on the inner electrode covered with the ionic liquid gel, and vacuum dried at 50°C for 6 hours to obtain a linear coaxial structure supercapacitor.

[0068] Example 6

[0069] Mix the activated carbon and acetylene black conductive agent thoroughly, then add polyacrylic acid binder and water, and stir at room temperature for 24 hours to form a slurry. The mass fractions of activated carbon, conductive agent and binder are ensured to be 85%, 5% and 10% respectively;

[0070] 18 mg of the slurry was evenly coated on a carbon fiber line with a diameter of 0.2 cm and a length of 6 cm. At the same time, an equal amount of the slurry was evenly coated on a nickel foil with a width of 1 cm and a length of 6 cm. The activated carbon-coated carbon fiber line and nickel foil were obtained by vacuum drying at 80°C for 24 hours.

[0071] 0.52 g of vinylidene fluoride-hexafluoropropylene copolymer and 1.86 g of N-methoxyethyl-N-methyldiethylammonium tetrafluoroborate were dissolved in 5 mL of acetone and stirred at room temperature for 10 hours to obtain a viscous ionic liquid gel electrolyte;

[0072] The carbon fiber wire coated with activated carbon is used as the inner electrode, and a dense layer of ionic liquid gel electrolyte is evenly coated on its surface;

[0073] The nickel foil coated with activated carbon was used as the outer electrode, evenly wrapped on the inner electrode covered with the ionic liquid gel, and vacuum dried at 50°C for 6 hours to obtain a linear coaxial structure supercapacitor.

[0074] Example 7

[0075] Mix the activated carbon and acetylene black conductive agent thoroughly, then add polyacrylic acid binder and water, and stir at room temperature for 24 hours to form a slurry. The mass fractions of activated carbon, conductive agent and binder are ensured to be 85%, 5% and 10% respectively;

[0076] 18 mg of the slurry was evenly coated on a carbon fiber line with a diameter of 0.2 cm and a length of 6 cm. At the same time, an equal amount of the slurry was evenly coated on a nickel foil with a width of 1 cm and a length of 6 cm. The activated carbon-coated carbon fiber line and nickel foil were obtained by vacuum drying at 160° C. for 24 hours.

[0077] 0.52 g of vinylidene fluoride-hexafluoropropylene copolymer and 1.86 g of N-methoxyethyl-N-methyldiethylammonium tetrafluoroborate were dissolved in 5 mL of acetone and stirred at room temperature for 10 hours to obtain a viscous ionic liquid gel electrolyte;

[0078] The carbon fiber wire coated with activated carbon is used as the inner electrode, and a dense layer of ionic liquid gel electrolyte is evenly coated on its surface;

[0079] The nickel foil coated with activated carbon was used as the outer electrode, evenly wrapped on the inner electrode covered with the ionic liquid gel, and vacuum dried at 50°C for 6 hours to obtain a linear coaxial structure supercapacitor.

[0080] Example 8

[0081] Mix the activated carbon and acetylene black conductive agent thoroughly, then add polyacrylic acid binder and water, and stir at room temperature for 24 hours to form a slurry. The mass fractions of activated carbon, conductive agent and binder are ensured to be 85%, 5% and 10% respectively;

[0082] 18 mg of the slurry was evenly coated on a carbon fiber line with a diameter of 0.2 cm and a length of 6 cm. At the same time, an equal amount of the slurry was evenly coated on a nickel foil with a width of 1 cm and a length of 6 cm. The activated carbon-coated carbon fiber line and nickel foil were obtained by vacuum drying at 120° C. for 24 hours.

[0083] 0.52 g of vinylidene fluoride-hexafluoropropylene copolymer and 1.86 g of N-methoxyethyl-N-methyldiethylammonium tetrafluoroborate were dissolved in 5 mL of acetone and stirred at room temperature for 10 hours to obtain a viscous ionic liquid gel electrolyte;

[0084] The carbon fiber wire coated with activated carbon is used as the inner electrode, and a dense layer of ionic liquid gel electrolyte is evenly coated on its surface;

[0085] The nickel foil coated with activated carbon was used as the outer electrode, evenly wrapped on the inner electrode covered with the ionic liquid gel, and vacuum dried at 40°C for 6 hours to obtain a linear coaxial structure supercapacitor.

[0086] Example 9

[0087] Mix the activated carbon and acetylene black conductive agent thoroughly, then add polyacrylic acid binder and water, and stir at room temperature for 24 hours to form a slurry. The mass fractions of activated carbon, conductive agent and binder are ensured to be 85%, 5% and 10% respectively;

[0088] 18 mg of the slurry was evenly coated on a carbon fiber line with a diameter of 0.2 cm and a length of 6 cm. At the same time, an equal amount of the slurry was evenly coated on a nickel foil with a width of 1 cm and a length of 6 cm. The activated carbon-coated carbon fiber line and nickel foil were obtained by vacuum drying at 120° C. for 24 hours.

[0089] 0.52 g of vinylidene fluoride-hexafluoropropylene copolymer and 1.86 g of N-methoxyethyl-N-methyldiethylammonium tetrafluoroborate were dissolved in 5 mL of acetone and stirred at room temperature for 10 hours to obtain a viscous ionic liquid gel electrolyte;

[0090] The carbon fiber wire coated with activated carbon is used as the inner electrode, and a dense layer of ionic liquid gel electrolyte is evenly coated on its surface;

[0091] The nickel foil coated with activated carbon was used as the outer electrode, uniformly wrapped on the inner electrode covered with ionic liquid gel, and vacuum dried at 60°C for 6 hours to obtain a linear coaxial structure supercapacitor.

[0092] The performance of the linear coaxial structure supercapacitor obtained in Examples 2-9 is similar to that in Example 1, and will not be described again here.

[0093] The above detailed description of the preferred specific embodiments of the present invention is only for illustrating the technical concept and features of the present invention, and its purpose is to enable those skilled in the art to understand the content of the present invention and implement it accordingly, and it cannot be used to limit the protection scope of the present invention. It should be understood that ordinary technicians in this field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in this technical field through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the protection scope determined by the claims.

Claims

1. A method for preparing a high voltage window linear coaxial structure supercapacitor, characterized in that: The high voltage window linear coaxial structure supercapacitor includes a carbon fiber wire located at the center and a nickel foil wrapped around the outer surface of the carbon fiber wire, wherein the space between the carbon fiber wire and the nickel foil is filled with an ionic liquid gel, wherein the carbon fiber wire serves as an inner electrode, the nickel foil serves as an outer electrode, the ionic liquid gel serves as a solid electrolyte, and the inner surface of the nickel foil is coated with activated carbon; The preparation method of the high voltage window linear coaxial structure supercapacitor comprises the following steps: S1, mixing activated carbon and conductive agent, then adding binder and water, stirring into slurry; S2, taking an equal amount of the slurry and uniformly coating it on a flexible carbon fiber wire and a nickel foil, respectively, and vacuum drying for 24 hours to obtain a carbon fiber wire and a nickel foil coated with activated carbon; S3, using N-methoxyethyl-N-methyldiethylammonium tetrafluoroborate to prepare an ionic liquid gel electrolyte; S4, using the carbon fiber wire coated with activated carbon obtained in S2 as an inner electrode, and coating a layer of dense ionic liquid gel electrolyte on its surface; S5, using the nickel foil coated with activated carbon obtained in S2 as an outer electrode, and evenly wrapping it on the inner electrode covered with ionic liquid gel obtained in S3, to obtain a linear coaxial structure supercapacitor; In the slurry prepared in S1, the mass fractions of activated carbon, acetylene black conductive agent and polyacrylic acid binder are 85%, 5% and 10% respectively; The diameter of the carbon fiber line is 0.2 cm and the length is 3-9 cm; The width of the nickel foil is 1 cm and the length is 4~8 cm.

2. The method for preparing a high voltage window linear coaxial structure supercapacitor according to claim 1, characterized in that: In S4, the carbon fiber wire coated with the ionic liquid gel is dried at a temperature of 40-60°C.

3. The method for preparing a high voltage window linear coaxial structure supercapacitor according to claim 1, characterized in that: In S2, the drying temperature is 80-160°C.

Citation Information

Patent Citations

  • supercapacitor

    US20150340169A1